The price of indiscretion eaudiobook - Maxwell, Cathy (Cameron Sisters, 2020)
New York Times and USA Today bestselling author Cathy Maxwell delivers another passionate romance that is sure to delight her dedicated fans. When three impoverished young ladies brought up in America decide to fulfill their late mother's dream of successful marriages and seasons, they concentrate their resources on sending the prettiest to London to make a brilliant match. But whom does she see but the man who had broken her heart years before? Alexander Haddon is no longer the rough and tumble man she once fell for, but a wealthy gentleman whose passionate nature is only just hidden under a veneer of sophistication . . . Contains mature themes.